2014
DOI: 10.1080/09064710.2014.898783
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of hydrolases, oxidase, and lyase in susceptible and resistant cucumber cultivars systemically induced with plant growth-promoting fungi against anthracnose

Abstract: Susceptible and resistant cultivars of cucumber (cv. Suyo and cv. Shogoin fushinari, respectively) were evaluated for induction of systemic resistance by plant growth-promoting fungal isolates Phoma sp. GS8-1 and nonsporulating fungus GU21-2 against Colletotrichum orbiculare. Reduction in anthracnose disease was assessed at regular intervals of 0, 3, 6, and 9 days after challenge inoculation. Activities of endochitinase, β-1, 3-endoglucanase, peroxidase (PO), polyphenol oxidase, and phenylalanine ammonia lyase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Certain beneficial microorganisms such as plant growth-promoting fungi (PGPF) have received great attention in the past few years due to not only promoting plant growth but also motivating the plant systemic resistance against different plant pathogens (Van Loon et al 1998;Elsharkawy et al 2014Elsharkawy et al , 2015Hassan et al 2014), nematode pests (Sikora 1988) and insect pests (Zehnder et al 1997). Recently, PGPF have been shown to induce systemic resistance in cucumber (Elsharkawy et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Certain beneficial microorganisms such as plant growth-promoting fungi (PGPF) have received great attention in the past few years due to not only promoting plant growth but also motivating the plant systemic resistance against different plant pathogens (Van Loon et al 1998;Elsharkawy et al 2014Elsharkawy et al , 2015Hassan et al 2014), nematode pests (Sikora 1988) and insect pests (Zehnder et al 1997). Recently, PGPF have been shown to induce systemic resistance in cucumber (Elsharkawy et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an increment in the defenserelated enzymes, that are, POX and PPO and total protein contents was observed in rice cultivars as a result of inoculation with T. barclayana. Among induced defense responses, production and accumulation of pathogensis related proteins are very important (Van Loon et al, 2006;Elsharkawy et al, 2012a, b;Elsharkawy et al, 2013;Hassan et al, 2014). Attempts have been made to exploit these anti-fungal proteins to develop disease resistant transgenic crop plants (Lin et al, 1995;Tabei et al, 1997).…”
Section: Relationship Between the Tested Rice Cultivars And Isolates mentioning
confidence: 99%
“…It was reported that plants defend themselves from the invader pathogens by either their structural barriers or antimicrobial compound which prevent colonization of the tissues. The induced defense responses include hypersensitive responses, the production of reactive oxygen species (ROS), pathogensis-related protein and ion fluxes across the plasma membrane (Zhao et al, 2005;Elsharkawy et al, 2012a, b;Elsharkawy et al, 2013;Hassan et al, 2014).…”
mentioning
confidence: 99%
“…Plant growth promoting fungi (PGPF) are a group of non‐pathogenic soil living saprophytes. It was reported that PGPF improve growth with the ability to manage plant diseases . Several strategies were investigated to control the pathogens by biological means.…”
Section: Introductionmentioning
confidence: 99%